2014
DOI: 10.1371/journal.pone.0087011
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Pre-Treatment Serum AFP-L3% in Hepatocellular Carcinoma: Systematic Review and Meta-Analysis

Abstract: BackgroundSerum lens culinaris agglutinin-reactive fraction of α-fetoprotein (AFP-L3%) has been widely used for HCC diagnosis and follow-up surveillance as tumor serologic marker. However, the prognostic value of high pre-treatment serum AFP-L3% in patients with hepatocellular carcinoma (HCC) remains controversial. We therefore conduct a meta-analysis to assess the relationship between high pre-treatment serum AFP-L3% and clinical outcome of HCC.MethodsEligible studies were identified through systematic litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 34 publications
3
50
0
Order By: Relevance
“…[2830] On the other hand, p53 is mutated in 25% of HCC patients. We demonstrated that AFP-L3 levels were higher in HCC patients with tumors expressing wt -p53 compared to those with tumors showing mutant -p53.…”
Section: Discussionmentioning
confidence: 99%
“…[2830] On the other hand, p53 is mutated in 25% of HCC patients. We demonstrated that AFP-L3 levels were higher in HCC patients with tumors expressing wt -p53 compared to those with tumors showing mutant -p53.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al. . presented in their meta‐analysis that high pretreatment serum AFP‐L3 levels indicated a poor prognosis, and AFP‐L3 may have significant prognostic value in patients with HCC having a low AFP concentration.…”
Section: Discussionmentioning
confidence: 99%
“…AFP has been considered as an ideal marker for diagnosis of HCC from the 1960s [4]. AFP could also be used for monitoring the treatment efficacy and recurrence of HCC [54]. Previous studies indicated that combination of two or three HCC markers might greatly improve the sensitivity and diagnostic accuracy [55,56,57].…”
Section: The Significance and Marker For Hcc Diagnosismentioning
confidence: 99%